Sensitization to the Effects of Tumor Necrosis Factor-α: Neuroendocrine, Central Monoamine, and Behavioral Variations - Hayley, Shawn (J Neurosci, 1999)
Consistent with the proposition that cytokines act as immunotransmitters between the immune system and the brain, systemic administration of the proinflammatory cytokine tumor necrosis factor-α (TNF-α; 1.0–4.0 μg) induced mild illness in CD-1 mice, increased plasma corticosterone concentrations, and altered central norepinephrine, dopamine, and serotonin turnover. The actions of TNF-α were subject to a time-dependent sensitization effect. After reexposure to a subeffective dose of the cytokine (1.0 μg) 14–28 d after initial treatment, marked illness was evident (reduced consumption of a palatable substance and diminished activity and social exploration), coupled with an elevation of plasma corticosterone levels. In contrast, cytokine reexposure 1–7 d after initial treatment did not elicit illness, and at the 1 d interval the corticosterone response to the cytokine was reduced. The increase of norepinephrine release within the paraventricular nucleus of the hypothalamus, as reflected by elevated accumulation of 3-methoxy-4-hydroxyphenylglycol, was augmented at the longer reexposure intervals. In contrast, within the central amygdala and the prefrontal cortex TNF-α reexposure at the 1 d interval was associated with a pronounced sensitization-like effect, which was not apparent at longer intervals. Evidently, systemic TNF-α proactively influences the response to subsequent treatment; however, the nature of the effects (i.e., the behavioral, neuroendocrine, and central transmitter alterations) vary over time after initial cytokine treatment. It is suggested that the sensitization may have important repercussions with respect to cognitive effects of TNF-α and may also be relevant to analyses of the neuroprotective or neurodestructive actions of cytokines.